Spreading cyber-autocracy?: The Shanghai Cooperation Organization and the diffusion of norms of “Internet sovereignty” - Harnisch, Sebastian (Authoritarian gravity centers, 2020)
Are authoritarian gravity centers undermining democracy by expanding their reach and scope beyond the limits of their own authority? Or does expansionist